Body-mass index and incidence of type 1 and type 2 diabetes in children and young adults in the UK: an observational cohort study. (November 2016) - Abbasi, Ali; Juszczyk, Dorota; van Jaarsveld, Cornelia H M; Gulliford, Martin C
Abstract: Background: Obesity, a global health issue at all ages, is a main risk factor for diabetes in adults, but little is known about the associations between obesity and trends in the incidence of the disease in children and young adults. We aimed to examine the recent incidence of type 1 and type 2 diabetes and associations between high body-mass index (BMI) and the incidence of each type of diabetes in children and young adults. Methods: We conducted cohort and nested case-control studies within a cohort of participants with a BMI record (369 362 individuals aged 2–15 years) using data from family practices contributing to the UK Clinical Practice Research Datalink between 1994 and 2013. Incident type 1 and type 2 diabetes were defined with medical diagnostic codes, prescriptions for antidiabetic medication, or glycated haemoglobin values of 6·5% or more. Poisson regression was used to test for diabetes incidence rates and trends. We estimated odds ratio for diabetes using data on cases and controls matched for year of birth, sex, and general practice. Findings: There were 654 incident cases of type 2 diabetes and 1318 incident cases of type 1 diabetes. The incidence of type 2 and type 1 diabetes increased from 6·4 per 100 000 person-years (95% CI 3·5–10·7, n=14) and 38·2 (30·4–47·2, n=84) in 1994–98 to 33·2 (29·7–37·1, n=320) and 52·1 (47·6–56·9, n=502) in 2009–13, respectively. The incidence of type 2 diabetes continued to increase in overweight (85th–95th percentile for age-specific and sex-specific BMI, p=0·015) or obese (≥95th percentile, p<0·0001) individuals through 1994–2013. Obese individuals (47·1% of type 2 diabetes cases, n=308) had a higher risk of incident type 2 diabetes than did individuals with normal BMI (odds ratio 3·75, 95% CI 3·07–4·57), and incidence rate ratio was 4·33 (95% CI 3·68–5·08). There was no consistent association between obesity and the incidence of type 1 diabetes. Interpretation: Increasing obesity is contributing to the rising incidence of type 2 but not type 1 diabetes among children and young adults in the UK, with a four times greater risk of developing type 2 diabetes in those who are obese. Funding: National Institute for Health Research.